PEMBERDAYAAN KADER UTAMA PC IPNU IPPNU KABUPATEN BANYUMAS DALAM ADVOKASI KEBIJAKAN PUBLIK - Ranjani Ranjani; Andri Trianfano; Sartono Sartono; Suryoto Suryoto (PARADIGMA: Jurnal Pengabdian Kepada Masyarakat, 2024)
Public policy issues in the form of regulations or government legal actions that cause problems in the community certainly require advocacy. PC IPNU IPPNU Banyumas Regency is one of the community organizations that has an important role in the sustainability of various public policies in Banyumas Regency. Weak understanding of policy problems and public policy advocacy strategies. Many public/government policies, both in the form of regulations, decisions, or government actions that violate or harm the public/community. Many cases occur, so that the ability to analyze these cases is needed. This service is carried out with the aim of assisting the Main Cadres of PC IPNU IPPNU Banyumas Regency. This activity was carried out from March to June 2024. The main target of this activity is the Main Cadres of PC IPNU IPPNU Banyumas Regency. This activity is carried out through several stages, starting from surveys and field studies, then activity planning is carried out which includes administrative preparation, preparation of activity budget plans and updating of socialization materials. After the implementation of this community service, PC IPNU IPPNU Banyumas Regency and all its members, especially its main cadres understand the importance of public policy advocacy, types of policies and steps in formulating public policies. The community enthusiastically welcomed the material presented, then spread understanding and knowledge related to public policy advocacy especially for the Main Cadres of PC IPNU IPPNU Banyumas Regency.